Population and Epidemiological Aspects of Carriage of Toxigenic (Cd tox+) and Non-toxigenic (Cd tox-) Diphtheria corynebacteria - E. A. Shmeleva; A. V. Melekhova; A. V. Saphronova (Эпидемиология и вакцинопрофилактика)
Relevance. It is known that antitoxic immunity saves from diphtheria, but does not prevent the carriage of Cd (tox+). Asymptomatic carriers of Cd (tox+) play a major role in maintaining the epidemiological process of diphtheria infection.Aims. Characteristics of the population composition and specifics of the kinetic reactions of Cd (tox-) and Cd (tox+) simultaneously functioning among people.Results. The functional features of the specific kinetic reactions of individual populations play an important role in the existence of microbial populations in human biotopes. The introduction of the corinephage tox+ gene into the symbiotic individual Cd (tox-) promoted the synthesis of the toxin and the adaptive stability of the Cd (tox-) population in the environment. Metabolites Cd (tox-) - autostabilizers of microbial growth form microecological symbiotic systems of human biotopes.Conclusions. The use of the metabiotic drug Kodivac from symbiotic Cd (tox-) allows: to treat long-term carriers of Cd (tox+); reduce circulation of Cd (tox+) in the population; together with small doses of diphtheria toxoid to create protection against diphtheria; form symbiogenesis in human biotopes, suppressing dysbiotic inflammatory reactions.